2023
DOI: 10.21203/rs.3.rs-2455413/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Combined adenovirus and Mycoplasma pneumoniae infection is an independent risk factor for developing severe community-acquired pneumonia in children

Abstract: Background: To investigate the pathogenic characteristics and risk factors of pediatric severe community-acquired pneumonia (CAP). Methods:We retrospectively analyzed the clinical data of hospitalized children with severe CAP, including sex, age, results of sputum or bronchoalveolar lavage fluid (BALF) bacterial and fungal cultures, respiratory viruses, serum Mycoplasma pneumoniae (MP)-IgM and Chlamydia Pneumoniae (CP)-IgM, and BALF or blood (1-3)-β-D-glucan/galactomannan test. Results:679 children with severe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
1
0
0
Order By: Relevance
“…In severe cases, this can result in multi-organ failure and circulatory metabolic disorders. These results are consistent with previous studies (22)(23)(24). Spaeder and Fackler also observed that children with severe HAdV pneumonia had elevated AST levels and decreased ALB levels, which were indicative of liver damage caused by adenovirus infection (25).…”
Section: Discussionsupporting
confidence: 92%
“…In severe cases, this can result in multi-organ failure and circulatory metabolic disorders. These results are consistent with previous studies (22)(23)(24). Spaeder and Fackler also observed that children with severe HAdV pneumonia had elevated AST levels and decreased ALB levels, which were indicative of liver damage caused by adenovirus infection (25).…”
Section: Discussionsupporting
confidence: 92%